A systematic overview of prefabricated construction policies in China. (20th January 2021) - Luo, Ting; Xue, Xiaolong; Wang, Yuna; Xue, Weirui; Tan, Yongtao
Abstract: The construction industry faces the challenges of balancing environmental concerns with the construction of new buildings. Although the government has identified the promotion of prefabricated construction as an important strategy for tackling this challenge, little attention has been paid by the government to the practical schemes to be used. To fill this gap, a systematic review was conducted of policies related to prefabricated construction in China. In this study, a policy reviewed framework for the prefabricated construction was established. A total of 133 prefabricated construction policies issued from 1956 to 2018 were reviewed by mixed content analysis. The results reveal a closely integrated policy network, the evolution of ambitious policy objectives, and the development of a combination of various policy instruments over the different stages. The most often employed prefabricated construction policy instrument was the standard. Initiatives and guidance were moderately used. The establishment of regulations has been largely ignored in China. In addition, although a diverse range of incentives has been offered, incentives were found to be the least frequently used due to their associated fiscal burdens on governments. Based on our results, a roadmap is proposed for optimizing the existing prefabricated construction policies. The findings of this study increase our understanding of construction policies and how to optimize the existing policies to promote prefabricated construction in China. The study also provides a valuable reference for the large-scale promotion of prefabricated construction in other countries and regions. Highlights: A policy reviewed framework for the prefabricated construction was established. 133 prefabricated construction policies in China were reviewed via mixed content analysis. The structure of the policy network, the evolution of policy objectives and policy instruments were investigated. A roadmap for optimizing the prefabricated construction policies was developed. The findings provide a valuable information resource for other countries and regions.